2022
DOI: 10.7185/geochemlet.2209
|View full text |Cite
|
Sign up to set email alerts
|

Early precipitated micropyrite in microbialites: A time capsule of microbial sulfur cycling

Abstract: Microbialites are organosedimentary rocks that have occurred throughout the Earth's history. The relationships between diverse microbial metabolic activities and isotopic signatures in biominerals forming within these microbialites are key to understanding modern biogeochemical cycles, but also for accurate interpretation of the geologic record. Here, we performed detailed mineralogical investigations coupled with NanoSIMS (Nanoscale Secondary Ion Mass Spectrometry) analyses of pyrite S isotopes in mineralisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Our results demonstrate that pyrite is a sensitive recorder of the diagenetic evolution of pore water sulfide in marine sediments, as suggested by previous studies ( 1 5 , 29 , 30 , 36 ). That the magnitude of intergrain isotopic variability in modern marine sedimentary pyrite populations can be so large (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results demonstrate that pyrite is a sensitive recorder of the diagenetic evolution of pore water sulfide in marine sediments, as suggested by previous studies ( 1 5 , 29 , 30 , 36 ). That the magnitude of intergrain isotopic variability in modern marine sedimentary pyrite populations can be so large (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3A). This calculated e mic approaches the expected equilibrium fractionation between sulfate and sulfide at the temperature of the studied sediments (35), which is much larger than reconstructions of e mic that are based on prior bulk sampling work ( 14) but consistent with SIMS-based findings from other localities (36). Despite the profound environmental changes across glacial-interglacial regimes, nearly constant e mic values indicate no substantive change in the activity of sulfatereducing microbes.…”
Section: S Pyr Variationssupporting
confidence: 75%
“…While some initial studies using this method reported sample size requirements of 100 nmol to 5 μmol sulfur (Ono et al., 2006; Paris, Fehrenbacher, et al., 2014) more recent workers have been able to push this limit down to 20 nmol (Au Yang et al., 2016). Alternatively, an ion microprobe can be used for measuring sulfur isotopes of geological samples in situ (Mojzsis et al., 2003; Whitehouse et al., 2005), and this technique has even been optimized for finely disseminated sulfides in S‐poor rock samples (Bryant et al., 2019; Marin‐Carbonne et al., 2022). These in situ techniques are vital for understanding multiple generations of sulfides that can exist in Archean rocks, and for distinguishing fluid‐rock interactions and diagenetic and recrystallization histories (Mojzsis et al., 2003; Whitehouse et al., 2005).…”
Section: Introductionmentioning
confidence: 99%